2022
DOI: 10.1002/mus.27745
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind placebo‐controlled pilot study of immunoglobulin for small fiber neuropathy associated with TS‐HDS and FGFR‐3 autoantibodies

Abstract: Introduction/Aims Small fiber neuropathies (SFN) have been associated with two autoantibodies, trisulfated heparin disaccharide (TS‐HDS) and fibroblast growth factor receptor 3 (FGFR‐3), and intravenous immune globulin (IVIG) has been suggested as a potential therapy. The study objective is to determine the efficacy of IVIG on nerve density, pain and neurologic examinations in patients with SFN associated with TS‐HDS and FGFR‐3 autoantibodies. Methods This was a double‐blind placebo‐controlled pilot study. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 23 publications
(58 reference statements)
0
30
0
Order By: Relevance
“…intravenous Ig also improved symptoms in case series of Sjögren’s-associated and coeliac-associated small fibre neuropathy by 1–3 points on clinical rating scales, although symptoms returned on intravenous Ig cessation in those with coeliac disease 114. Two intravenous Ig trials in patients with TS-HDS and FGFR3 antibodies reported that 10 out of 12 treated participants had improved pain scores and/or higher ENFD on skin biopsy114; although, as outlined above, a more recent randomised controlled trial found no difference between intravenous Ig and placebo in this same group 32. An intravenous Ig trial in small fibre neuropathy attributed to inflammatory/dysimmune causes, either because of a previously diagnosed autoimmune disorder, or the presence of one or more abnormal blood markers associated with autoimmunity, also showed efficacy: intravenous Ig reduced QSART abnormalities from 70% to 50% and reduced 0–10 pain scores by 1 point 115.…”
Section: Management Advancesmentioning
confidence: 95%
See 1 more Smart Citation
“…intravenous Ig also improved symptoms in case series of Sjögren’s-associated and coeliac-associated small fibre neuropathy by 1–3 points on clinical rating scales, although symptoms returned on intravenous Ig cessation in those with coeliac disease 114. Two intravenous Ig trials in patients with TS-HDS and FGFR3 antibodies reported that 10 out of 12 treated participants had improved pain scores and/or higher ENFD on skin biopsy114; although, as outlined above, a more recent randomised controlled trial found no difference between intravenous Ig and placebo in this same group 32. An intravenous Ig trial in small fibre neuropathy attributed to inflammatory/dysimmune causes, either because of a previously diagnosed autoimmune disorder, or the presence of one or more abnormal blood markers associated with autoimmunity, also showed efficacy: intravenous Ig reduced QSART abnormalities from 70% to 50% and reduced 0–10 pain scores by 1 point 115.…”
Section: Management Advancesmentioning
confidence: 95%
“…Trisulfated heparin disaccharide (TS-HDS) antibodies have been reported in as many as 37% of patients with idiopathic small fibre neuropathy,29 antiplexin D1 antibodies in 12.7% of patients30 and antibodies against the fibroblast growth factor receptor 3 (FGFR3) in up to 15% 31. However, it should be noted that a recent placebo-controlled study of intravenous immunoglobulin (Ig) in small fibre neuropathy with TS-HDS and FGFR3 autoantibodies found that nerve fibre density on skin biopsy and neuropathy clinical scores did not significantly improve, potentially calling their role in pathogenesis into question 32. Importantly, this was a pilot study and larger trials are needed.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…11 In this issue of the Journal, Gibbons and colleagues present a double-blind, placebo-controlled study evaluating the efficacy of IVIg on nerve density, pain, and neuropathy scores in patients with SFN associated with TS-HDS and FGFR-3 autoantibodies. 12 The small (8 patients given IVIg, 9 given placebo) pilot study treated patients with 2 g/kg, followed by 1 g/kg every 3 weeks for a total of six treatments. After 6 months, there was no difference between the IVIg and placebo groups in the primary outcome, which was intraepidermal nerve fiber density.…”
mentioning
confidence: 99%
“…Intravenous immunoglobulin for immune-mediated small fiber neuropathy with TS-HDS and FGFR-3 antibodies: The jury is still out I read with great interest the recent pilot study by Gibbons and colleagues regarding intravenous immunoglobulin (IVIg) in presumed immune-mediated small fiber neuropathy (SFN) with trisulfated heparin disaccharide Ido2SGlcNS-6S (TS-HDS) and fibroblast growth factor 3 (FGFR-3) autoantibodies. 1 It was laudable in the midst of the COVID-19 pandemic that the authors recruited and carried out the study, and they should be congratulated. Their article does make some excellent points about the pitfalls of skin biopsy positivity in patients without clinical evidence of SFN, an uncritical approach regarding commercial biopsy testing results that have not been repeated, as well as the need for further research to clarify the pathogenicity of these novel antibodies.…”
mentioning
confidence: 99%
“…One major issue is the study's power, as the authors stated, "This study was not powered to prove efficacy in most of the study end-points…" 1 There was subject attrition due to the pandemic, and only 17 subjects completed the study out of the planned 20. 1 However, in preparation for an upcoming similar clinical trial (NCT04153422), we completed a power analysis revealing that at least 20 subjects need to be enrolled (10 IVIg and 10 placebo) to yield a power of 80% and show a statistically significant difference in intraepidermal nerve fiber density (IENFD). Enrolling up to 26 patients to account for a potential 20% attrition rate is ideal to ensure adequate power.…”
mentioning
confidence: 99%